ST-Elevation Mimicking Myocardial Infarction in a Sepsis Condition: A Diagnostic Dilemma - Alfiona, Lekenila; Herbert, Manurung Joel (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2025)
Sepsis-induced myocardial injury can clinically mimic an ST-Elevation Myocardial Infarction (STEMI), presenting a critical diagnostic dilemma. This descriptive qualitative case study aimed to elucidate this phenomenon and highlight appropriate clinical management. The research focused on a single, purposively selected patient: a 31- year-old male with sepsis from a scrotal abscess who presented with chest pain, ST-segment elevation on electrocardiogram (ECG), and significantly elevated cardiac troponins. Data from the patient's medical records, including serial ECGs and coronary angiography results, were analyzed descriptively. Primary percutaneous coronary intervention (PCI) was correctly deferred due to the sepsis condition. Following surgical debridement of the abscess, the patient's ECG normalized, and subsequent angiography confirmed the absence of coronary stenosis. This case demonstrates that sepsis-induced global ischemia can masquerade as a myocardial infarction. The conclusion is that clinicians must consider non-coronary etiologies for ST-elevation in septic patients to prevent misdiagnosis and ensure that appropriate, life-saving infection management is not delayed.